Local immunomodulation combined to radiofrequency ablation results in a complete cure of local and distant colorectal carcinoma. (4th March 2019) - Lemdani, Katia; Mignet, Nathalie; Boudy, Vincent; Seguin, Johanne; Oujagir, Edward; Bawa, Olivia; Peschaud, Frédérique; Emile, Jean-François; Capron, Claude; Malafosse, Robert
ABSTRACT: Radiofrequency ablation (RFA) of colorectal liver metastases activates a specific T-cell response that is ineffective in avoiding recurrence. Recently, local immunomodulation garnered interests as a way to improve the immune response. We were interested in improving the RFA immune response priming to propose a curative treatment of colorectal cancer (CRC) based on antitumor immunity. First, we demonstrated that the RFA did not increase the tumor infiltrating lymphocytes in secondary distant tumors of patients and in mice model and could not avoid relapse. Remarkably, RFA and in situ immunomodulation with GM-CSF-BCG hydrogel induced complete cure of microscopic secondary lesions in mice, related to a strong specific immune response. Then, we demonstrated that the immune escape of large secondary lesions was reversed by addition of the systemic PD-1 blockade to the in situ immunomodulation. The lack of an effective distant immune response in patients treated with RFA confirmed the relevance of this new combination strategy. Increasing the in situ priming response of radiofrequency ablation provides effective adjuvants to induce an abscopal effect. In the case of large lesions, synergy between PD1 blockade inhibitor, ineffective alone or after single RFA, with in situ immunomodulation, could lead to reconsideration of the use of checkpoint inhibition in metastatic MSS CRC.